Carotid Duplex Study of the Left External Carotid Artery Transposition for the Repair of the Left Internal Carotid Artery Aneurysm. Issue 3 (September 2019) - Noh, Cassey Y.
This case study reports a carotid duplex study of a rare case of the extracranial internal carotid artery aneurysm, and an unconventional procedure for the repair, transposition of the external carotid artery into the internal carotid artery. The pre-operative and post-operative computed tomography images confirm these findings.